Total Talar Replacement With Custom-Made Vitallium Prosthesis for Talar Avascular Necrosis - Luo, Wenbin; Zhang, Hanyang; Han, Qing; Li, Zhaoyan; Zhong, Zhuan; Jia, Guoliang; Liu, Yuxuan; Chang, Fei; Wang, Jincheng (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The current study investigated the application of three-dimensional (3D) printing technology in the treatment of talar avascular necrosis (TAN). Custom-made Vitallium talar prostheses were designed and generated via 3D printing. We hypothesized that these talar prostheses would facilitate more stable positioning, better ergonomically fit the ankle joint surfaces, and promote favorable long-term prognoses. Material and methods: Computed tomography scans of both ankle joints were acquired from three patients diagnosed with TAN. The talar on the unaffected side was used as the design blueprint. Hence, with the aid of 3D printing technology a customized talar prosthesis made from a novel Vitallium alloy could be manufactured for each individual patient. Results: In all three cases there were no signs of prosthesis loosening or substantial degenerative change in the surrounding area of the joint, but small osteophytes were observed on the tibial side and navicular side. No chronic infection or other prosthesis-related complications were observed in any of the patients. All three were able to walk without pain at the most recent follow-up. Conclusions: With the aid of 3D printing and a novel Vitallium alloy, total talar replacement achieved encouraging results in 3/3 patients. All patients were satisfied with their joint function, and were able to return to their daily activities without limitations. Although more cases and longer-term follow-up periods are required, the success rate reported herein is encouraging.